Low-dielectric polyamide acid porous microsphere / polyimide composite film and preparation method thereof

By preparing polyamic acid porous microspheres without thermal imidation and blending with polyamic acid solution to imidize, the problem of uneven dispersion of existing low-dielectric polyimide film fillers is solved, and high quality is achieved The low-dielectric polyamic acid porous microspheres/polyimide composite film improves its application performance.

CN119463237APending Publication Date: 2025-02-18UNIV OF ELECTRONICS SCI & TECH OF CHINA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411501962.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

When adding filler, the chemical difference between the filler and the polyamic acid solution leads to rapid precipitation of porous microspheres in the solution and uneven dispersion, resulting in poor film quality and limited application.

Method used

Polyamic acid porous microspheres without thermal imidation were prepared by reacting dianhydride and diamine monomer, and blended with polyamic acid solution to imidize, taking advantage of the high chemical similarity between the two. , achieve better dispersion and high incorporation.

Benefits of technology

The quality and application performance of low-dielectric polyamic acid porous microspheres/polyimide composite films are significantly improved, the dispersion and interface compatibility of the film are enhanced, the dielectric constant is reduced, and the comprehensive performance of the material is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463237A_ABST
    Figure CN119463237A_ABST
Patent Text Reader

Abstract

The invention relates to the field of low-dielectric polyimide film modification, in particular to a low-dielectric polyamide acid porous microsphere / polyimide composite film and a preparation method thereof. Polyamic acid porous microspheres which are not subjected to thermal imidization are prepared through the reaction of diamine and dianhydride monomers, then the polyamic acid porous microspheres and a polyamic acid solution are subjected to blending imidization, and due to the fact that the polyamic acid porous microspheres and the polyamic acid solution both have a large number of-CO-NH-and-COOH groups, the chemical similarity is high, and the polyamic acid porous microspheres and the polyamic acid solution have excellent dispersity and high doping amount; and compared with other fillers, the filler is more stable in a film matrix, has more excellent dispersity and interfacial compatibility, and does not need surface modification. Meanwhile, the polyamic acid porous microspheres can better fix crack propagation in the fracture process of the material, and the toughening effect is achieved; and the porous structure is embedded into the film substrate, so that air can be introduced, the dielectric constant of the substrate material can be remarkably reduced, and the film has more excellent comprehensive performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of low dielectric polyimide film modification, and in particular to a low dielectric polyamic acid porous microsphere / polyimide composite film and a preparation method thereof. Background Art

[0002] Polyimide PI is a polymer material formed by the polycondensation of dianhydride and diamine, and contains repeating units of imide ring and benzene ring in the molecular chain. Due to its structural characteristics such as rigid conjugated molecular chain structure, strong intermolecular force, low single bond polarization, and high bond energy of chemical bonds such as CN and C=O in the imide ring, it usually has excellent dielectric properties, and also has good mechanical properties, thermal properties, and chemical stability. Therefore, polyimide can be used in many fields such as 5G communications, aerospace, integrated circuits, etc., and is often further modified into low dielectric polyimide film for application.

[0003] In the existing low-dielectric polyimide film technology, when a low-dielectric polyimide composite film is prepared by adding fillers and blending with a polyamic acid solution, for example, when a polyimide porous microsphere is blended with a polyamic acid solution, the amide group and the carboxyl group in the polyimide porous microsphere are dehydrated into an imide ring. This is because there is a large chemical difference between the filler polyimide porous microsphere and the polyamic acid solution, which causes the porous microsphere to precipitate quickly and disperse unevenly in the polyamic acid solution. Therefore, the low-dielectric polyimide film prepared by adding fillers has poor quality (uniformity), which limits its application. Summary of the invention

[0004] In view of the above-mentioned problems or deficiencies, in order to solve the problem of poor quality of existing low-dielectric polyimide films, the present invention provides a low-dielectric polyamic acid porous microsphere / polyimide composite film and a preparation method thereof. The present invention prepares polyamic acid by reacting dianhydride and diamine monomers, uses a polyamic acid aqueous solution as a continuous phase and liquid paraffin as an oil phase to form a polyamic acid emulsion, and then obtains polyamic acid porous microspheres after washing, centrifugation, and freeze-drying; then the polyamic acid porous microspheres are used as fillers and blended with the polyamic acid solution to obtain a low-dielectric polyamic acid porous microsphere / polyimide composite film.

[0005] A method for preparing a low dielectric polyamic acid porous microsphere / polyimide composite film comprises the following steps:

[0006] Step 1, preparation of polyamic acid porous microspheres:

[0007] Polyamic acid (PAA) is prepared by polycondensation reaction in a non-polar solvent using dianhydride and diamine as reaction monomers in a ratio of 1:1 to 1.5, and then an organic amine (such as triethylamine) is added to salify the polyamic acid, with the molar ratio of the organic amine to the diamine monomer being 2:1.

[0008] Then the obtained polyamic acid is dissolved in water with a solid content of 1.5-5.0 wt% to obtain a PAA aqueous solution. With the polyamic acid aqueous solution as the continuous phase, liquid paraffin is dispersed into small droplets in the polyamic acid aqueous solution under the action of a hydrophilic surfactant to form a heavy emulsion.

[0009] The emulsion is then dispersed in liquid paraffin containing a lipophilic surfactant to form a polyamic acid emulsion; finally, acetic anhydride and pyridine are added, and the polyamic acid porous microspheres are obtained after washing, centrifugation and freeze-drying.

[0010] Among them, the mass ratio of liquid paraffin to polyamic acid aqueous solution is 1:2-6; the mass ratio of hydrophilic surfactant to polyamic acid aqueous solution is 1:16-47; the mass ratio of liquid paraffin to single emulsion is 1:1.2-2.4; the mass ratio of lipophilic surfactant to single emulsion is 1:15-40; and the volume ratio of acetic anhydride to pyridine is 1:1.

[0011] Step 2, preparation of low dielectric polyamic acid porous microspheres / polyimide composite film: using dianhydride and diamine monomers as reaction monomers to react at low temperature in a non-polar solvent to prepare a polyamic acid solution; placing the polyamic acid porous microspheres prepared in step 1 in the same non-polar solvent, adding the polyamic acid solution after ultrasonic dispersion, and stirring to obtain a uniformly dispersed polyamic acid porous microsphere / polyamic acid mixed solution;

[0012] The obtained polyamic acid porous microsphere / polyamic acid mixed solution is uniformly coated on a substrate (such as a glass substrate); then after eliminating bubbles (such as vacuum heating conditions), a low dielectric polyamic acid porous microsphere / polyimide composite film is obtained by further heating through a gradient heating program, and the upper limit of the gradient heating temperature is 300°C.

[0013] Furthermore, the solid content of the porous polyamic acid microspheres in the low-dielectric polyamic acid porous microspheres / polyimide composite film is 3-20 wt %. The higher the solid content, the lower the dielectric of the composite film.

[0014] Furthermore, the gradient temperature increase program is to maintain the temperature at 100° C. for 0.5 to 2 h, then increase the temperature to 200° C. for 0.5 to 2 h, and then increase the temperature to 250° C. for 0.5 to 2 h.

[0015] Furthermore, the dianhydride monomer is one or a combination of pyromellitic anhydride (PMDA), hexafluoroisopropylphthalic anhydride (6FDA), 4,4'-oxydiphthalic anhydride (ODPA), 4,4'-phenylenedioxydiphthalic anhydride (HQDA), and 3,3',4,4'-biphenyltetracarboxylic anhydride (BPDA).

[0016] Furthermore, the diamine monomer is one or a combination of 4,4'-diaminodiphenyl ether (ODA), 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl (TFMB), p-phenylenediamine, 2,2'-bis[4-(4-aminophenoxyphenyl)]propane (BAPP), and 1,3-bis(4'-aminophenoxy)benzene (TPE-R).

[0017] Furthermore, the hydrophilic surfactant is one of octylphenol polyoxyethylene ether (OP-10), pentadecylphenol polyoxyethylene ether (OP-15), and eicosylphenol polyoxyethylene ether (OP-20); the lipophilic surfactant is one of sorbitan monooleate (Span-80), sorbitan trioleate (Span-85), sorbitan monopalmitate (Span-65), and sorbitan monostearate (Span-60).

[0018] Furthermore, the non-polar solvent in step 1 is one of N,N-dimethylacetamide (DMAc), N,N-dimethylformamide (DMF), and N-methylpyrrolidone (NMP).

[0019] Existing low dielectric polyimide composite film generally adopts polyimide PI as filler, and the present invention adopts dianhydride and diamine monomer reaction to prepare polyamic acid that is not subjected to thermal imidization, and makes the form of porous microsphere as filler, when polyamic acid porous microsphere and polyamic acid solution are blended and co-imidized to prepare composite film, because both have a large amount of amide groups (-CO-NH-) and carboxyl (-COOH) groups, thus porous microsphere has more excellent dispersibility and high incorporation amount in polyamic acid solution. Because the embedded filler is a porous structure, air can be introduced, thereby can significantly reduce the dielectric constant of composite material. Compared with polyimide porous microsphere, polyamic acid porous microsphere has excellent dispersibility and interface compatibility in matrix, and does not need surface modification, and at the same time, it can also better fix crack extension in the fracture process of material, play toughening effect, and can better improve the comprehensive performance of matrix.

[0020] In summary, the present invention uses dianhydride and diamine monomers as reaction monomers to prepare polyamic acid porous microspheres, and uses them as reinforcing fillers. The polyamic acid porous microspheres have a large number of amide groups (-CO-NH-) and carboxyl groups (-COOH) and have a high chemical similarity with the polyamic acid solution. Therefore, they have better dispersibility and high incorporation amount, thereby blending and co-imidizing to obtain high-quality low-dielectric polyamic acid porous microspheres / polyimide composite films, making them more suitable for 5G communications, aerospace, integrated circuits and other fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1This is a SEM photograph of the polyamic acid porous microspheres obtained in Example 1.

[0022] Figure 2 The FTIR spectra of the two porous microspheres obtained in Example 1 and Comparative Example 2 are compared.

[0023] Figure 3 This is a physical comparison diagram of the film-forming solutions of Comparative Example 1, Comparative Example 2, Example 1 and Example 2.

[0024] Figure 4 The cross-sectional SEM photos of the films finally obtained in Comparative Example 1, Comparative Example 2, Example 1 and Example 2 are shown.

[0025] Figure 5 The dielectric properties of the films obtained in Examples 1 and 2 vary with the content of polyamic acid porous microspheres.

[0026] Figure 6 It is a low-field nuclear magnetic resonance test curve diagram of the film-forming mixed solution of Example 1 and Comparative Example 2. DETAILED DESCRIPTION

[0027] The present invention is further described in detail below with reference to the accompanying drawings and embodiments.

[0028] Example 1

[0029] This embodiment provides a low dielectric polyamic acid porous microsphere / polyimide composite film, wherein the polyamic acid porous microsphere has a structural repeating unit as shown below:

[0030]

[0031] The preparation method is as follows:

[0032] Step 1, preparation of polyamic acid porous microspheres:

[0033] Weigh 0.01 mol of 4,4'-diaminodiphenyl ether (ODA) and dissolve it in 50 ml of N,N-dimethylacetamide (DMAc) under a nitrogen atmosphere, then add 0.01 mol of pyromellitic anhydride (PMDA) and stir the reaction at 0°C for 6 hours to obtain a polyamic acid solution; then add 2.78 ml of triethylamine (TEA) to salt the polyamic acid.

[0034] The reaction product was washed at least 3 times with acetone, and then vacuum dried at room temperature to obtain a polyamic acid salt solid (PAAS). Weigh 0.6g of polyamic acid salt solid and dissolve it in a solution consisting of 14ml deionized water and 0.5ml triethylamine as an intermediate water continuous phase. The prepared intermediate aqueous phase was added dropwise to a solution consisting of 5ml liquid paraffin and 0.3ml octylphenol polyoxyethylene ether, and rapidly stirred and emulsified for 30min as a heavy emulsion. The emulsion was added to a solution consisting of 60ml liquid paraffin and 0.5ml sorbitol monooleate, and rapidly stirred and emulsified for 10min to prepare a polyamic acid emulsion.

[0035] The product was washed at least three times with petroleum ether, centrifuged and freeze-dried to obtain a polyamic acid porous microsphere powder with good dispersibility. Figure 1 This is a scanning electron microscope photograph of the polyamic acid porous microspheres in Example 1. It can be seen that there are a large number of complete and rich pore structures in the polyamic acid porous microspheres, with high specific surface area and porosity, and the particle size is between 5 and 20 μm.

[0036] Step 2: Preparation of low dielectric polyamic acid porous microspheres / polyimide composite film:

[0037] Weigh 0.01 mol of 4,4'-diaminodiphenyl ether (ODA) and dissolve it in 50 ml of N,N-dimethylacetamide (DMAc) under nitrogen atmosphere, then add 0.01 mol of pyromellitic anhydride (PMDA) and stir the reaction at 0°C for 6 hours to obtain a polyamic acid solution. Weigh 0.324 g of the polyamic acid porous microspheres prepared in step 1 in 50 ml of N,N-dimethylacetamide (DMAc), ultrasonically disperse for 30 minutes, then add the polyamic acid solution and stir for 2 hours to obtain a uniformly dispersed polyamic acid porous microsphere / polyamic acid mixed solution.

[0038] The obtained mixed solution is then evenly coated on a glass plate. After eliminating bubbles under vacuum heating conditions, it is further heated through a gradient temperature increase program (maintaining at 100°C for 1 hour, then heating to 200°C for 1 hour, and then heating to 250°C for 1 hour) to obtain a low dielectric polyamic acid porous microsphere / polyimide composite film with a high doping content of polyamic acid porous microspheres.

[0039] Example 2

[0040] Compared with Example 1, the present example is different in that: in step 2, 0.761 g of the polyamic acid porous microspheres prepared in step 1 are weighed into 50 ml of N,N-dimethylacetamide (DMAc). The remaining steps are the same as those in Example 1.

[0041] Comparative Example 1

[0042] Weigh 0.01 mol of 4,4'-diaminodiphenyl ether (ODA) and dissolve it in 50 ml of N,N-dimethylacetamide (DMAc) under nitrogen atmosphere, then add 0.01 mol of pyromellitic anhydride (PMDA) and stir the reaction at 0°C for 6 hours to obtain a polyamic acid solution. The obtained solution is then evenly coated on a glass plate, and after eliminating bubbles under vacuum heating conditions, the polyimide film is further heated through a gradient heating program (maintaining at 100°C for 1 hour, heating to 200°C for 1 hour, and then heating to 250°C for 1 hour).

[0043] Comparative Example 2

[0044] This comparative example provides a polyimide porous microsphere / polyimide film, wherein the polyimide porous microsphere has a structural repeating unit as shown below:

[0045]

[0046] The preparation method is as follows:

[0047] Compared with Example 1, this comparative example has the following differences:

[0048] In step 1, the obtained polyamic acid porous microsphere powder is thermally imidized: under a nitrogen atmosphere, the temperature is naturally reduced to room temperature through a gradient temperature program (maintained at 100°C for 1 hour, then heated to 200°C for 1 hour, and then heated to 300°C for 1 hour), and finally polyimide porous microspheres are obtained.

[0049] In step 2, 0.324 g of the polyimide porous microspheres prepared in step 1 were weighed into 50 ml of N, N-dimethylacetamide (DMAc), and after ultrasonic dispersion for 30 min, the polyamic acid solution was added and stirred for 2 h to obtain a uniformly dispersed polyimide porous microsphere / polyamic acid mixed solution. The obtained mixed solution was then evenly coated on a glass plate, and after eliminating bubbles under vacuum heating conditions, the polyimide porous microsphere / polyimide composite film was obtained after further heating through a gradient heating program (maintaining at 100° C. for 1 h, heating to 200° C. for 1 h, and then heating to 250° C. for 1 h).

[0050] Figure 2 FTIR spectra of the two porous microspheres prepared in Example 1 and Comparative Example 2 are compared. As can be seen from the figure, the 1663 cm -1 The peaks correspond to the characteristic absorption peaks of the C=O bond of the carboxyl (-COOH) group in polyamic acid, 1606 and 1550 cm -1The peaks correspond to the characteristic absorption peaks of C=O and CN bonds of the amide group (-CO-NH-) in polyamic acid, indicating that the polyamic acid porous microspheres have a large number of amide groups (-CO-NH-) and carboxyl groups (-COOH). However, the FTIR spectrum of the polyimide porous microspheres prepared in Comparative Example 2 does not show these three characteristic absorption peaks. Therefore, when the polyamic acid porous microspheres are blended with the polyamic acid solution to prepare a composite film, since both have a large number of amide groups and carboxyl groups, the polyamic acid porous microspheres have better dispersibility and high incorporation amount in the polyamic acid solution.

[0051] Figure 3 The following are physical comparison diagrams of the polyamic acid porous microspheres / polyamic acid mixed solutions of Examples 1 and 2, and the polyamic acid solution of Comparative Example 1, and the polyamic acid porous microspheres / polyamic acid mixed solution of Comparative Example 2. As can be seen from the figure, the polyimide porous microspheres in Comparative Example 2 have already had microsphere precipitation on the second day of standing, while the polyamic acid porous microspheres in Examples 1 and 2 have no precipitation. After standing for fifteen days, the polyimide porous microspheres in Comparative Example 2 are almost completely precipitated, while the polyamic acid porous microspheres in Examples 1 and 2 have no obvious precipitation. This shows that the polyamic acid porous microspheres are more stable in the polyamic acid solution, have better dispersibility, and can achieve a high incorporation amount.

[0052] Figure 4 The cross-sectional SEM photos of the polyimide film of Comparative Example 1, the polyimide porous microsphere / polyimide composite film of Comparative Example 2, and the polyamic acid porous microsphere / polyimide composite film of Examples 1 and 2. Wherein (a) is the cross-sectional SEM photo of the polyimide film of Comparative Example 1, (b) is the cross-sectional SEM photo of the polyimide porous microsphere / polyimide composite film of Comparative Example 2, and (c) and (d) are cross-sectional SEM photos of the polyamic acid porous microsphere / polyimide composite film of Examples 1 and 2. As can be seen from the figure, the polyimide porous microspheres in the composite film of Comparative Example 2 have obvious agglomeration phenomenon, while the polyamic acid porous microspheres in the composite films of Examples 1 and 2 are well dispersed. It is explained that in the polyimide substrate, the polyamic acid porous microspheres are more stable than the polyimide porous microspheres, and it is not easy to agglomerate and precipitate, and the fracture toughening effect of the polyamic acid porous microspheres in the film substrate is more obvious.

[0053] Figure 5The dielectric constant comparison curves of the polyamic acid porous microsphere / polyimide composite film of Example 1 and Example 2 and the polyimide film of Comparative Example 1 are shown. (a) is a graph showing the change in dielectric constant, and (b) is a graph showing the change in dielectric loss. It can be seen from the curves in the figure that within the frequency range of 10 to 10M, the dielectric constant of the film decreases as the mass fraction of the polyamic acid porous microspheres increases. This is because the porous structure of the microspheres introduces air with a dielectric constant of 1, which significantly reduces the dielectric constant of the film substrate.

[0054] Figure 6 The low-field nuclear magnetic resonance test curves of the polyamic acid porous microspheres / polyamic acid mixed solutions and the polyimide porous microspheres / polyamic acid mixed solutions of Example 1 and Comparative Example 2 show that the smaller the relaxation rate change, the better the stability and step-by-step nature of the system; the curve of the stability and dispersibility of the mixed solution over time is measured using low-field nuclear magnetic resonance technology. As can be seen from the figure, compared to Comparative Example 2, the relaxation rate (R2) of Example 1 is substantially unchanged and changes less, indicating that the polyamic acid porous microspheres in the system of Example 1 are very stable in the polyamic acid solution, and the dispersibility is better, so that a high incorporation amount can be achieved.

[0055] According to the above specific implementation scheme and test analysis results, the present invention provides a new type of low-dielectric polyamic acid porous microsphere / polyimide composite film and its preparation method. The present invention prepares polyamic acid porous microspheres that have not been thermally imidized by reacting diamine and dianhydride monomers, and then blends the polyamic acid porous microspheres with the polyamic acid solution for co-imidization. Since both have a large number of -CO-NH- and -COOH groups, they have high chemical similarity and excellent dispersibility and high incorporation amount; compared with other fillers, they are more stable in the film matrix, have better dispersibility and interface compatibility, and do not require surface modification. At the same time, the polyamic acid porous microspheres can better fix the crack extension during the fracture process of the material, and play a toughening role; and since the porous structure is embedded in the film matrix, air can be introduced, thereby significantly reducing the dielectric constant of the matrix material, so that the film has better comprehensive performance.

Claims

1. A method for preparing a low dielectric polyamic acid porous microsphere / polyimide composite film, characterized in that: The following steps are involved: Step 1, preparation of polyamic acid porous microspheres: Using dianhydride and diamine as reaction monomers in a ratio of 1:1 to 1.5 to perform polycondensation in a non-polar solvent to prepare polyamic acid PAA, and then adding organic amine to salt the polyamic acid, with the molar ratio of the organic amine to the diamine monomer being 2:1; Then the obtained polyamic acid is dissolved in water with a solid content of 1.5-5.0 wt% to obtain a PAA aqueous solution, with the polyamic acid aqueous solution as a continuous phase, and liquid paraffin is dispersed into small droplets in the polyamic acid aqueous solution under the action of a hydrophilic surfactant to form a heavy emulsion; The emulsion is then dispersed in liquid paraffin containing a lipophilic surfactant to form a polyamic acid emulsion; finally, acetic anhydride and pyridine are added, and the polyamic acid porous microspheres are obtained after washing, centrifugation and freeze-drying; Among them, the mass ratio of liquid paraffin to polyamic acid aqueous solution is 1:2-6; the mass ratio of hydrophilic surfactant to polyamic acid aqueous solution is 1:16-47; the mass ratio of liquid paraffin to single emulsion is 1:1.2-2.4; the mass ratio of lipophilic surfactant to single emulsion is 1:15-40; and the volume ratio of acetic anhydride to pyridine is 1:

1. Step 2: Preparation of low dielectric polyamic acid porous microspheres / polyimide composite film: A polyamic acid solution is prepared by reacting dianhydride and diamine monomers in a non-polar solvent at low temperature; the polyamic acid porous microspheres prepared in step 1 are placed in the same non-polar solvent, and after ultrasonic dispersion, the polyamic acid solution is added, and a uniformly dispersed polyamic acid porous microsphere / polyamic acid mixed solution is obtained after stirring; The obtained polyamic acid porous microsphere / polyamic acid mixed solution is uniformly coated on a substrate; then after eliminating bubbles, a low dielectric polyamic acid porous microsphere / polyimide composite film is obtained by further heating through a gradient heating program, and the upper limit of the gradient heating temperature is 300°C.

2. The method for preparing the low dielectric polyamic acid porous microsphere / polyimide composite film according to claim 1, characterized in that: The organic amine is triethylamine.

3. The method for preparing the low dielectric polyamic acid porous microsphere / polyimide composite film according to claim 1, characterized in that: The air bubbles are eliminated by vacuum heating.

4. The method for preparing the low dielectric polyamic acid porous microsphere / polyimide composite film according to claim 1, characterized in that: The solid content of the polyamic acid porous microspheres in the low-dielectric polyamic acid porous microsphere / polyimide composite film is 3-20 wt %. The higher the solid content, the lower the dielectric of the composite film.

5. The method for preparing the low dielectric polyamic acid porous microsphere / polyimide composite film according to claim 1, characterized in that: The gradient temperature increase program is to keep the temperature at 100° C. for 0.5 to 2 h, then heat to 200° C. and keep the temperature at 0.5 to 2 h, and then heat to 250° C. and keep the temperature at 0.5 to 2 h.

6. The method for preparing the low dielectric polyamic acid porous microsphere / polyimide composite film according to claim 1, characterized in that: The dianhydride monomer is one or a combination of pyromellitic anhydride (PMDA), hexafluoroisopropylphthalic anhydride (6FDA), 4,4'-oxydiphthalic anhydride (ODPA), 4,4'-phenylenedioxydiphthalic anhydride (HQDA), and 3,3',4,4'-biphenyltetracarboxylic anhydride (BPDA).

7. The method for preparing the low dielectric polyamic acid porous microsphere / polyimide composite film according to claim 1, characterized in that: The diamine monomer is one or a combination of 4,4'-diaminodiphenyl ether (ODA), 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl (TFMB), p-phenylenediamine, 2,2'-bis[4-(4-aminophenoxyphenyl)]propane (BAPP), and 1,3-bis(4'-aminophenoxy)benzene (TPE-R).

8. The method for preparing the low dielectric polyamic acid porous microsphere / polyimide composite film according to claim 1, characterized in that: The hydrophilic surfactant is one of octylphenol polyoxyethylene ether (OP-10), pentadecylphenol polyoxyethylene ether (OP-15), and eicosylphenol polyoxyethylene ether (OP-20); the lipophilic surfactant is one of sorbitan monooleate (Span-80), sorbitan trioleate (Span-85), sorbitan monopalmitate (Span-65), and sorbitan monostearate (Span-60).

9. The method for preparing the low dielectric polyamic acid porous microsphere / polyimide composite film according to claim 1, characterized in that: The non-polar solvent in step 1 is one of N,N-dimethylacetamide (DMAc), N,N-dimethylformamide (DMF) and N-methylpyrrolidone (NMP).

10. A method for preparing a low dielectric polyamic acid porous microsphere / polyimide composite film, characterized in that: The method is prepared by any one of claims 1 to 9.